Malignancy within a Tail Gut Cyst: A Case of Retrorectal Carcinoid Tumour. (13th November 2014) - Abukar, A. A.; Parcell, B. J.; Lim, C. B.; Patil, P. V.; Ramsanahie, A.; Carey, F.; Steele, R. J. C.; Thaha, M. A.
Abstract : Purpose. Tailgut cysts with malignant transformation are rare entities. We discuss the diagnostic strategy and treatment of a malignancy within a tailgut cyst. Methods. In this study we report on the case of a 61-year-old man with a malignant neuroendocrine tumour arising within a tailgut cyst and an overview of the literature emphasising the histopathological characteristics and differential diagnosis. Results. Our patient presented with lower back pain, rectal pain, and increased urgency of defecation. MRI scan and CT-guided biopsy on histological analysis revealed a diagnosis of carcinoid tumour of the presacral space. The patient subsequently underwent an abdominoperineal excision of the rectum. Conclusions. This case highlights the importance of tailgut cysts as a differential diagnosis of presacral masses. It is a rare congenital lesion developing from remnants of the embryonic postanal gut and is predominantly benign in nature. Approximately half of cases remain asymptomatic; therefore, diagnosis is often delayed. Magnetic resonance imaging is the investigation of choice and an awareness of the possibility of malignant potential is critical to avoiding missed diagnosis and subsequent morbidity. Complete surgical excision allows accurate diagnosis, confirmation of oncological clearance, and prevention of mortality.